Proteins journey—from marine to freshwater ecosystem: blood plasma proteomic profiles of pink salmon Oncorhynchus gorbuscha Walbaum, 1792 during spawning migration - Kochneva, Albina; Efremov, Denis; Murzina, Svetlana A. (Frontiers in Physiology, 2023)
The pink salmon (Oncorhynchus gorbuscha) is a commercial anadromous fish species of the family Salmonidae. The species has a peculiar life cycle that includes spawning migration from marine to freshwater environments, which is accompanied by significant adaptive changes in the body, both the physiological and biochemical. This study described and revealed the variability of blood plasma proteomes of female and male pink salmon collected from three different biotopes - marine, estuarine and riverine - that the fish pass through spawning migration. Identification and comparative analysis of pink salmon blood plasma protein profiles were performed using proteomic and bioinformatic approaches. Blood proteomes of female and male spawners collected from different biotopes were qualitatively and quantitatively distinguished. Females differed primarily by proteins associated with reproductive system development (certain vitellogenin and choriogenin), lipid transport (fatty acid binding protein) and energy production (fructose 1,6-bisphosphatase), and males - by proteins involved in blood coagulation (fibrinogen), immune response (lectins) and reproductive processes (vitellogenin). Differentially expressed sex-specific proteins were implicated in proteolysis (aminopeptidases), platelet activation (β- and γ-chain fibrinogen), cell growth and differentiation (a protein containing the TGF_BETA_2 domain) and lipid transport processes (vitellogenin and apolipoprotein). The results obtained are of fundamental and practical importance, providing to the existing knowledge of biochemical adaptations to spawning of pink salmon, representative of the economically important migratory fish species.